An Evaluation of the Implementation of Reschedule Policy in Portfolio at Risk (PAR) Control at PT. PNM Mekaar Regional Blitar - Tutik Hidayati; A. Dewantoro Marsono (Formosa Journal of Social Sciences (FJSS), 2023)
Troubled financing at PT. PNM Mekaar Regional Blitar can occur due to internal factors and external factors. Internal factors are factors that come from within the company itself, such as weak analysis and supervision of customer financing. External factors are factors that are beyond the control of the company's management, such as the character of untrustworthy customers and natural disasters. The implementation of a rescheduling policy for customers with problems is expected to control the PAR value. Based on the phenomena that occur, researchers conduct research on evaluating the application of rescheduling policies in controlling PAR values. This study uses a descriptive qualitative approach. Sources of data used in this study consisted of primary data and secondary data. Data collection was obtained through observation, interviews and documentation. Data analysis through three paths: data reduction, data presentation, conclusion and verification